2017
DOI: 10.1101/157628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compressive Temporal Summation in Human Visual Cortex

Abstract: Combining sensory inputs over space and time is fundamental to vision. Population receptive field models have been successful in characterizing spatial encoding throughout the human visual pathways. A parallel question-how visual areas in the human brain process information distributed over timehas received less attention. One challenge is that the most widely used neuroimaging method-fMRIhas coarse temporal resolution compared to the time-scale of neural dynamics. Here, via carefully controlled temporally mod… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 69 publications
6
62
0
Order By: Relevance
“…Many models describe how monotonic or tuned responses could arise [6,38,39]. Early human visual cortex exhibits monotonic responses to visual event duration and frequency [1,2], from which tuned responses can be straightforwardly derived [40]. Our results show correlated and interacting selectivity for event duration and period (a measure of frequency).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Many models describe how monotonic or tuned responses could arise [6,38,39]. Early human visual cortex exhibits monotonic responses to visual event duration and frequency [1,2], from which tuned responses can be straightforwardly derived [40]. Our results show correlated and interacting selectivity for event duration and period (a measure of frequency).…”
Section: Discussionmentioning
confidence: 62%
“…Tested models included selectivity for temporal frequency; event duration and period; event period and occupancy (proportion of that period the event filled; i.e., period/duration); and event duration and inter-event interval (time from event offset to the next event onset; i.e., periodÀduration). We also compared logarithmic and linear response functions, and monotonic amplitude increases with occupancy (i.e., sustained neural response component) and/or event onset frequency (i.e., transient components) [1,2].…”
Section: Timing-selective Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…A task that focuses attention continuously at a center of fixation was a trivial candidate for this goal because such tasks were previously shown to reduce saccade rate (Pastukhov & Braun, ) and are often used in visual studies for other purposes. For instance, some fMRI studies use foveal tasks to focus attention at the center while measuring brain responses to task‐irrelevant peripheral stimulation (e.g., Goense & Logothetis, ; Watanabe et al, ; Yuval‐Greenberg & Heeger, ; Zhou, Benson, Kay, & Winawer, ). These studies demonstrated the plausibility of studying brain responses to task‐irrelevant parafoveal stimulation while attention is engaged in the fovea.…”
Section: Discussionmentioning
confidence: 99%